Clinical utility of circulating tumor cells: an update. Issue 6 (25th December 2020) - Vasseur, Antoine; Kiavue, Nicolas; Bidard, François‐Clément; Pierga, Jean‐Yves; Cabel, Luc
Abstract : The prognostic role of circulating tumor cells (CTCs) has been clearly demonstrated in many types of cancer. However, their roles in diagnostic and treatment strategies remain to be defined. In this review, we present an overview of the current clinical validity of CTCs in nonmetastatic and metastatic cancer, and the main studies or concepts investigating the clinical utility of CTCs. In particular, we focus on breast, lung, colorectal, and prostate cancer. Two major topics concerning the clinical utility of CTC are discussed: treatment based on CTC count or CTC variations, and treatment based on the molecular characteristics of CTCs. Although some of these studies are inconclusive, many are still ongoing, and their results could help to define the role of CTCs in the management of cancers. A summary of published or ongoing phase II‐III trials is also presented. Abstract : This review article discusses the clinical utility of circulating tumor cells (CTCs) in various settings of screening and treatment of non‐metastatic and metastatic tumors. Two major aspects are considered, namely i) treatment based on CTC count or CTC variations, and ii) treatment based on the molecular characteristics of CTCs. A summary of published or ongoing phase II‐III trials with CTCs is also presented.